Effects of a back squat training program on leg power, jump, and sprint performances in junior soccer players - Chelly, M. S.; Fathloun, M.; Cherif, N.; Amar, M. B.; Tabka, Z.; Van Praagh, E. (The Journal of Strength and Conditioning Research, 2009)
The aim of the present study was to investigate the effects of voluntary maximal leg strength training on peak power output (Wpeak), vertical jump performance, and field performances in junior soccer players. Twenty-two male soccer players participated in this investigation and were divided into 2 groups: A resistance training group (RTG; age 17 +/- 0.3 years) and a control group (CG; age 17 +/- 0.5 years). Before and after the training sessions (twice a week for 2 months), Wpeak was determined by means of a cycling force-velocity test. Squat jump (SJ), countermovement jump (CMJ), and 5-jump test (5-JT) performances were assessed. Kinematics analyses were made using a video camera during a 40-m sprint running test and the following running velocities were calculated: The first step after the start (Vfirst step), the first 5 m (Vfirst 5 meters), and between the 35 m and 40 m (Vmax). Back half squat exercises were performed to determine 1-repetition maximum (1-RM). Leg and thigh muscle volume and mean thigh cross-sectional area (CSA) were assessed by anthropometry. The resistance training group showed improvement in Wpeak (p < 0.05), jump performances (SJ, p < 0.05 and 5-JT, p < 0.001), 1-RM (p < 0.001) and all sprint running calculated velocities (p < 0.05 for both Vfirst step and Vfirst 5 meters, p < 0.01 for Vmax). Both typical force-velocity relationships and mechanical parabolic curves between power and velocity increased after the strength training program. Leg and thigh muscle volume and CSA of RTG remained unchanged after strength training. Back half squat exercises, including adapted heavy loads and only 2 training sessions per week, improved athletic performance in junior soccer players. These specific dynamic constant external resistance exercises are highly recommended as part of an annual training program for junior soccer players.